Personality of parents with bipolar disorder and interpersonal functioning among their offspring: a prospective 10-year study - Ostiguy, Caroline; Hodgins, Sheilagh (Development and psychopathology, 2012)
A comparison of offspring of parents with bipolar disorder (OBD) and offspring of parents with no mental disorder (ONMD) showed that parents' neuroticism was associated with internalizing and externalizing problems among their children. The present study examined whether parents' neuroticism predicted poor interpersonal functioning among offspring 10 years later and whether the problems observed in middle childhood mediated the association between parents' neuroticism and offspring functioning. When offspring were in middle childhood, parents completed the revised NEO Personality Inventory and rated the child's behavior on the Child Behavior Checklist. Ten years later, 65 OBD and 59 ONMD completed interviews assessing mental disorders and interpersonal and noninterpersonal functioning. High neuroticism and low agreeableness in parents predicted poor interpersonal functioning in their offspring in late adolescence-early adulthood. The offspring's externalizing and internalizing problems in middle childhood partially mediated the association between parents' personality and offspring interpersonal functioning. Moreover, the association between parents' neuroticism and offspring internalizing problems was stronger among the OBD than the ONMD. Overall, the results suggested an intergenerational transmission of risk whereby high neuroticism and low agreeableness in parents were associated with behavioral problems among offspring in middle childhood that, in turn, predicted poor interpersonal functioning 10 years later.
Gesehen am 05.04.2018